2018
DOI: 10.1002/bit.26853
|View full text |Cite
|
Sign up to set email alerts
|

Local FK506 dose‐dependent study using a novel three‐dimensional organotypic assay

Abstract: Local administration of FK506, an FDA approved immunosuppressant with neuroregenerative properties, is a promising technique to achieve improved peripheral nerve regeneration while preventing the side effects associated with the systemic administration of this drug. Although considerable research has been devoted to the development of clinically suitable systems for local delivery of FK506 to the site of nerve injury and repair, the optimal dose of FK506 for enhancement of axon regeneration in the peripheral n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 35 publications
0
38
0
Order By: Relevance
“…FK‐506, an immunosuppressive drug, enhances nerve regeneration, as it increases the axonal growth rate in animal models . Now, approaches have been developed to provide FK506 locally to enhance axon regeneration given its abilities to stimulate more rapid axon outgrowth . This strategy is quite intriguing given that it reduces the potential for any systemic toxicity from its immunosuppression.…”
Section: Experimental Nerve Graft Alternativesmentioning
confidence: 99%
“…FK‐506, an immunosuppressive drug, enhances nerve regeneration, as it increases the axonal growth rate in animal models . Now, approaches have been developed to provide FK506 locally to enhance axon regeneration given its abilities to stimulate more rapid axon outgrowth . This strategy is quite intriguing given that it reduces the potential for any systemic toxicity from its immunosuppression.…”
Section: Experimental Nerve Graft Alternativesmentioning
confidence: 99%
“…11,39 Recently, Tajdaran et al studied the in vitro neurotrophic effects of FK506 when delivered globally to the cell body and axon growth cones and just locally to the axon growth cones. 34 They reported that global FK506 increased axon extension and density in a dose dependent manner, while local FK506 delivered to the axon growth cones similarly increased axon extension and density but not in a dose dependent manner. 40 has been shown to increase axon density by promoting collateral axon sprouting/branching, but a secondary inhibitory effect at higher concentrations that reduces axon elongation may explain the differences in gastrocnemius muscle mass and EMG amplitude.…”
Section: Discussionmentioning
confidence: 98%
“…34 They reported that global FK506 increased axon extension and density in a dose dependent manner, while local FK506 delivered to the axon growth cones similarly increased axon extension and density but not in a dose dependent manner. 40 has been shown to increase axon density by promoting collateral axon sprouting/branching, but a secondary inhibitory effect at higher concentrations that reduces axon elongation may explain the differences in gastrocnemius muscle mass and EMG amplitude. 25,40 In a previous in vitro study, we determined a dose-dependent effect that FK506 concentration had on neurite extension and reported a diminished effect at higher concentrations, with the highest used concentrations having no significant differences than no-drug controls.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations